Live Black Soldier Fly Larvae Ingestion In Broiler Chickens Growth Performance and Carcass Quality Characteristics - Brah, Nouri; Moussa, Ousseini Hassan; Zounon, Felix; Abdoulaye, Ousseina; Amadou, Laouali (International Journal of Poultry Science, 2025)
Objective: This study aimed to evaluate the effects of the gradual ingestion of live Black Soldier Fly Larvae (LBSFL) prior to feed distribution on the growth performance and carcass quality characteristics of broiler chickens. Materials and Methods: A total of 80 unsexed COBB 500 broiler chickens, 21 days of age, were used in a 4-week feeding trial. Birds were randomly assigned to 20 batches (4 birds per batch) housed in a 50 m² (10 m×5 m) poultry facility. Four dietary treatments were formulated: a control group without LBSFL supplementation (LBSFL0) and three experimental groups receiving 3 g (LBSFL3), 6 g (LBSFL6), or 9 g (LBSFL9) of live larvae per bird per day, administered prior to the distribution of the commercial feed. Each treatment was randomly allocated to five replicate batches. Growth performance parameters included feed intake, live body weight, Average Daily Gain (ADG) and Feed Conversion Ratio (FCR). Carcass characteristics measured were carcass weight and yield, viscera weight, full intestine weight, empty gizzard weight and liver yield. Orthogonal polynomial contrasts were applied to evaluate linear and quadratic effects of increasing LBSFL ingestion levels on growth and carcass parameters. Results: Feed intake and FCR were not significantly influenced by LBSFL supplementation (p>0.05). However, live body weight and ADG significantly increased (p<0.05) with higher levels of LBSFL ingestion. Among carcass characteristics, only the empty gizzard weight was significantly affected (p<0.05), while other organ and carcass yields remained unchanged (p>0.05). Conclusion: The inclusion of live Black Soldier Fly Larvae at levels up to 9 g per bird per day can be safely incorporated into broiler diets without adverse effects on growth performance or carcass quality. Further economic evaluation is recommended to determine the most cost-effective inclusion rate for commercial production.